Spatial Distribution and Spatial Determinants of Stunting Among Under-Five Children in West Sumatra Province - Ramadanti, Aztika; Djafri, Defriman; Pradipta, Yudi (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Stunting remains a major public health challenge because of its long-term impacts on growth, cognitive development, productivity, and future health. Marked differences in stunting prevalence across districts and municipalities in West Sumatra suggest spatial heterogeneity that cannot be adequately explained using conventional ecological approaches. This study aimed to examine the spatial distribution, spatial autocorrelation and spatial association between stunting among children under five and its ecological determinants in West Sumatra Province in 2024. An ecological study was conducted using secondary data from the West Sumatra Provincial Health Office and the Central Bureau of Statistics, covering all 19 districts and municipalities. Spatial patterns were analyzed using Global Moran's I and Bivariate Local Indicators of Spatial Association (LISA). The findings showed that stunting prevalence was predominantly moderate across the province. Global Moran's I indicated significant negative spatial autocorrelation (Moran's I = −0.245; p < 0.05), reflecting a dispersed spatial pattern. Bivariate LISA identified limited significant local associations, with clusters mainly classified as Low-Low and High-Low. These results suggest that stunting is influenced more by local contextual conditions than by geographic clustering, highlighting the need for geographically targeted and context-specific interventions to strengthen stunting prevention and control.